The "Pericope Adulterae" (John 7:53–8:11): Jesus’ Answer, an Offer of Life to Suffering Women - Rabie-Boshoff, Annelien (Perichoresis, 2021)
This article explores a probable motivation for the insertion of the Pericope Adulterae (John 7:53-8:11) in the Gospel of John in consideration of the motive of ‘living/life’ used by the gospel writer. Using John 8:12 as the starting point of this investigation, the article focuses on the warning to the Israelites against idolatry with specific attention to the warning against worshiping the sun, the moon, and the stars (Deuteronomy 4:15-20). It also deals with the Feast of Tabernacles, which is the direct context in which Jesus declared that he is the light of the world. The water ceremony also plays a central role in understanding the bigger picture that unfolds, as well as the Early Church’s struggle against heretical Christological teachings of who Jesus was with regard to his human nature and his divine nature.